Exploring individual differences in fear extinction in male and female mice: insights from HPA axis, microbiota, and transcriptomics - Marc Ten-Blanco; María Ponce-Renilla; Inmaculada Pereda-Pérez; Cristina Izquierdo-Luengo; Carlo Bressa; Olga Zafra; Rosa María Tolón; Fernando Berrendero (Translational Psychiatry)
Abstract Exposure to traumatic life events may compromise physical and mental health of specific subjects. While some individuals extinguish fear appropriately, others exhibit an inefficient and persistent fear response, with remarkable differences between sexes. Understanding the heterogeneity in fear extinction responses is essential for elucidating the underlying mechanisms of fear-related disorders. We used a multidisciplinary approach analyzing the hypothalamic-pituitary-adrenal (HPA) axis tone, the microbiota composition, and the transcriptome of the amygdala (primary brain region involved in fear regulation) in adult male and female mice that were exposed to the Pavlovian fear conditioning and extinction paradigm. This model allowed us to stratify the mice population into two extreme phenotypic subgroups (resilient and susceptible), based on their individual fear extinction behavior. Characterization of some components of the HPA axis revealed strong disturbances in vulnerable males (e.g., increased hypothalamic CRF mRNA and corticosterone plasma levels), whereas softer changes were found in female animals. Several bacterial groups such as the genera Parvibacter, Alloprevotella and Limosilactobacillus and the family Christensenellaceae were enriched in the microbiota of resilient males, as well as relevant bacterial taxa enrichment was also observed in resilient (genus Muribaculum) and susceptible (family Eggerthellaceae) female mice. We also identified clear differences in the transcriptomic profile of the amygdala (31 differentially expressed genes) in male animals. These findings underscore the intricate involvement of multiple factors shaping the inter-individual variability of fear extinction response in a sex-dependent manner, thus paving the way for new potential targets for fear-related disorders.